2017
DOI: 10.22270/jddt.v7i5.1513
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Therapeutic Applications of Phytosomes

Abstract: Ethnobotanical plants have been used in the treatment of various diseases since antiquity. The phytoconstituents have pharmacological activities such as anti-tumor, anti-inflammatory, antinociceptive, anti-obesity, thermoregulatory effects, cardioprotective, anti-asthmatic, anti-diabetic, anti-oxidant, hepatoprotective and potent CNS activities. Various drug delivery systems like liposomes, niosomes, transferosomes, ethosomes, phytosomes, colloidosomes etc. are developed in order to carry the drug to the site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…Our findings agreed with previous studies that reported the improved anticancer activity of Oleu and rutin when formulated as nanoparticles. [13,[41][42][43][44] The findings of this study are consistent with previous research, [29-31-42] demonstrating that nano-particles, particularly phytosomes, effectively enhance the solubility and stability of phyto-compounds. Consequently, this improvement leads to significantly enhanced bioavailability and activity levels.…”
Section: In Vitro Anticancer Activitysupporting
confidence: 92%
“…Our findings agreed with previous studies that reported the improved anticancer activity of Oleu and rutin when formulated as nanoparticles. [13,[41][42][43][44] The findings of this study are consistent with previous research, [29-31-42] demonstrating that nano-particles, particularly phytosomes, effectively enhance the solubility and stability of phyto-compounds. Consequently, this improvement leads to significantly enhanced bioavailability and activity levels.…”
Section: In Vitro Anticancer Activitysupporting
confidence: 92%
“…Phytoconstituents and the polar head of lipid react and form the complex that is further envelop by the non-polar part of lipid (Figure 3). Phytoconstituents generally consist of active hydrogen that binds with the polar part of phospholipid through hydrogen bonding and forms lipid-compatible vesicles 4 (Figure 4). An updated phospholipid complex of different active constituents and herbal extracts is shown in Table 3.…”
Section: Mechanism Of Phytosome Complex Formation 313mentioning
confidence: 99%
“…Numerous novel herbal vesicular delivery systems have been fruitfully developed in recent years, including liposomes, phytosomes, niosomes, tansferosomes, ethosomes and various other vesicular systems to meet the challenges. Drug targeting and the sustained release of the active molecule are made possible by vesicular drug delivery systems 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Casperome boswellia phytosome was applied as potent antiinflammatory agent, Ginkgo select herbosome as cognition enhancer and as antioxidant, hawthorn herbosome for cardiovascular health, sericoside herbosome as antiwrinkle and tonic and 'Meriva', a curcumin herbosome for healthy joints. The antioxidant and free radical scavenging activity of silipide phytosome of Silybum marianum showed hepatoprotective activity (Chivte et al, 2017). Recently, quercetin (polyphenol) phytosome was studied clinically and used in the treatment of COVID-19 where it increases oral absorption up to 20-fold than normal (Di Pierro et al, 2021).…”
Section: Phytosome In Healthcare Managementmentioning
confidence: 99%